Influence of different mechanisms of martensite aging on the features of martensitic transformations. Issue 12 (7th August 2015) - Kosogor, Anna; Lyange, Maria; Zadorozhnyy, Mikhail; Miki, Hiroyuki; Takagi, Toshiyuki; L'vov, Victor A.; Khovaylo, Vladimir
Abstract : Aging‐induced changes in the features of the calorimetric peak accompanying martensitic transformation were considered in the framework of phenomenological theory. Taking into account two different mechanisms of martensite aging, it was demonstrated that the domination of the internal axial stress contribution narrows the calorimetric peak and elevates its magnitude, while the prevalence of the internal pressure contribution broadens the calorimetric peak and diminishes its magnitude. The developed theoretical approach was applied to modeling of experimentally measured calorimetric peaks of Ni–Mn–Ga alloys.